Design and Validation of a Compact 3.5GHz Antenna for 5G-based IoT Applications - Najib Al-Fadhali, Najib Al-Fadhali; Huda Majid, Huda Majid; Jumadi, Jumadi; Mohammed. S. M. Gismalla, Mohammed. S. M. Gismalla (2023)
Compact and small-sized antennas are crucial for 5G-based IoT applications due to their ease of integration into devices with limited space, lower power consumption, and ease of installation in urban areas. In this research, we designed a compact wideband 3.5GHz antenna for 5G-based IoT applications using CST Studio software. The antenna was fabricated on an FR-4 substrate with dimensions of 40mmx32mm and a thickness of 1.6mm, with a microstrip feeding line. Simulation results showed a return loss of -42.287dB and a VSWR of 1.016. Real measurements of S11, radiation pattern, and gain were conducted to validate the simulation results, with S11 measurements taken using a Vector Network Analyzer at the UTHM Pagoh RF Lab and radiation pattern and gain measured in a chamber at the UTeM RF Lab. The simulation and real measurement results were similar, with slight differences due to device inaccuracies and manufacturing. The designed antenna is believed to be beneficial for fifth-generation communication-based IoT applications